The Relationship Between Leadership Style And Employee Performance In Permata Keluarga Jabadeka Hospitals - Ikhlasul Achyar Ajami; Oscar Jayanegara (Dinasti International Journal of Education Management And Social Science, 2024)
There are many challenges for health organizations in both countries, so it is necessary for them to have effective and strategic leadership practices. For employees, effective leadership is needed to develop strategies and structures that will motivate and inspire long-term employees, strengthen their commitments, and lower employee turnover.Despite setbacks and difficulties, a successful leadership style considers the organization's future, helps align employees' efforts and vision, and positively allocates both people and material resources toward the organization's objectives and interests. Examples of the several types of leadership styles, such as transformational, transactional, and charismatic leadership, are provided. With a sample size of thirty, this study employs a cross-sectional research methodology and is quantitative in nature. Data is gathered using questionnaires as primary data and document reviews as secondary data. Descriptive analysis techniques are used to portray the data quantitatively. The results of statistical testing chi-square obtained p-value = 0.00. It can be concluded that there is a significant relationship between leadership style and employee performance at the Permata Family Hospital in Jabadeka (p-value => 0.05).